Electronic certificates as authentic deeds Provisions governing as well as public doubts - Nursya, Nursya; Harwita, Harwita (Institute Of computer Science (IOCS), 2024)
Advances in digital technology continue to develop rapidly, this development will result in the birth of new legal products, one of which is the Regulation of the Minister of Agrarian Affairs / Head of BPN Number 1 of 2021 concerning electronic certificates, which was declared effective when it was announced in early 2021. This Ministerial Regulation refers to article 147 of Law Number 11 of 2020 concerning Work Creation. Polemics have occurred when linked to article 5 paragraph 4 of Law No. 11 of 2008 on ITE jo Law No. 19 of 2016 which rejects notarial deeds and PPAT deeds made in electronic form. Then with the existence of Law No. 1 of 2024 concerning the Second Amendment to the ITE Law at origin 5 paragraph 4 changing the norm that previously prohibited notary or PPAT products in electronic form and then submitting to the laws that regulate it, so that based on article 147 of the Ciptaker Law and article 5 paragraph 4 of the ITE Law No. 1 of 2024, electronic certificates can be declared as authentic deeds because these two regulations are in accordance with article 1868 BW concerning the form of authentic deeds. However, the Ministerial Regulation on electronic certificates is not yet compliant with BW, such as article 1866 BW which does not recognise the term electronic authentic deed, article 1886 BW on the submission of electronic authentic deeds in court and how to submit them if they are in electronic form, Article 137 HIR states that if the parties deny a deed in court, the deed must be produced before the judge, and preparations for producing the authentic deed in the form of an electronic certificate must include hardware such as a monitor to directly view the contents of the deed and software, namely the availability of a computer network for all courts in Indonesia. And what is very important is article 1888 BW, which states that the evidentiary power of a deed is in the original deed and not in an excerpt, copy or photocopy, while the electronic certificate of the original data is stored on the server, and the public only has an excerpt, unlike the analogue certificate of the original data is in the community. It is a hope for the public that the data will be secured by a reliable programme and strong IT security, so that it is not easily attacked by hackers.